المفكر الإسلامي الصيني الإمام الشهيد يوسف تشنغ كه لي: حياته، وأفكاره = Life and thoughts of Martyred Chinese Islamic thinker, Imam Yousuf Chen Ke Li - Ma Zhengbin, Yunus Abdullah (IIUM Press, International Islamic University Malaysia, 2014)
عُني هذا البحث بحياة المفكر الإسلامي الصيني الإمام الشهيد يوسف تشنغ كه لي وأفكاره الإصلاحيّة لرفع شأن أمة الإسلام في الصين خاصة، وفي العالم كلّه عامّة. وكان إخلاصه الممحض لله تعالى، وحبّه العميق للأمة ألإسلاميّة، وإيثار الآخرة على الدنيا يمثّل أهم مظهر لأفكاره وحياته. وقد التزم الباحث الأمانة العلمية في نقل المعلومات من المصادر الصينية، وعرض أفكار وآراء الإمام الشهيد يوسف تشنغ كه لي. ********************************************************* This research paper deals with the life of martyred Chinese Islamic thinker, Imam Yousuf Chen Ke Li, and his reformative ideas with a view to elevating the status of the Muslims in China in particular and in the whole world in general. His sincere devotion to Allah and deep love for the Muslim Ummah, and his preference of the afterlife to the present world constitute major features of his thoughts and life. The researcher has committed to scholarly integrity in transferring information from Chinese sources and presenting the intellectual ideas and opinions of Chen Ke Li. ********************************************************** Kajian ini berurusan dengan kehidupan seorang pemikir Cina Islam yang syahid, Imam Yousuf Chen Ke Li, dan idea-idea reformatifnya yang bertujuan meningkatkan taraf orang Islam khususnya di Cina dan secara amnya di seluruh dunia. Keihklasan ibadatnya kepada Allah, cinta mendalam bagi umat Islam, dan mengutamakan akhirat daripada dunia ini membentukkan ciri-ciri utama pemikiran dan hidupnya. Penyelidik kajian ini telah berkomited dengan integriti ilmiah dalam memindahkan maklumat daripada sumber-sumber Cina dan menyampaikan idea-idea intelektual dan pendapat Chen Ke Li.